2019
DOI: 10.1111/are.14024
|View full text |Cite
|
Sign up to set email alerts
|

Apparent digestibility coefficients of fungal fermented plant proteins in two different penaeid shrimps—A comparative study

Abstract: Using the 70:30 replacement method and chromium as an inert marker, the digestibility of four fermented oilseed meals/cakes (soybean meal (FSBM), groundnut oil cake (FGNC), rapeseed meal (FRSM), and sunflower oil cake (FSFC)) were determined in Penaeus monodon and Penaeus indicus. Apparent dry matter digestibility (ADMD) of fermented ingredients was ranked as FSBM > FGNC > FRSM > FSFC. The critical variations in apparent protein digestibility (APD) in P. monodon (0.816%) and P. indicus (0.608%) were lower than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…Dietary lipids had a significant influence on PER and PR, and the highest values were also obtained at the same lipid level (6.91%) to the growth performance in the current study. It is vitally important that protein is utilized for the synthesis of muscle tissue rather than for metabolic energy (Jannathulla et al, ). However, protein content in muscle of M. nipponense (Table ) was not significantly affected by the dietary lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary lipids had a significant influence on PER and PR, and the highest values were also obtained at the same lipid level (6.91%) to the growth performance in the current study. It is vitally important that protein is utilized for the synthesis of muscle tissue rather than for metabolic energy (Jannathulla et al, ). However, protein content in muscle of M. nipponense (Table ) was not significantly affected by the dietary lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to study the potential effect of fermented ingredients on the fed animals, digestibility trials were carried out in three penaeid shrimp species viz., P. vannamei (Jannathulla, Dayal, Ambasankar, & Muralidhar, ; Jannathulla, Dayal, Vasanthakumar, et al, ) and P. indicus, P. monodon (Jannathulla et al, ) . The nutritive value of ingredients, in terms of apparent digestibility coefficients of dry matter, crude protein, energy and amino acid were assessed using a dietary inclusion of 30% of test ingredients (untreated/fermented) within a reference diet (70%).…”
Section: Approaches For Utilization Of Plant Protein Sourcesmentioning
confidence: 99%
“…The microorganisms can be active under anaerobic conditions in order to dissimilate the ingredients organic contents (5). By this way the long chain amino acids and fatty acids can be shortened to be more available for absorption in the gastrointestinal tract of fish (17)(18)(19). It has been reported that the animal proteins (e.g., poultry feather meal, fish meal, and animal protein blend) fermented with various microorganisms such as fungus (Aspergillus sp.…”
Section: Introductionmentioning
confidence: 99%